Effect of Bismuth Sulfate Coated on Acidified CNT on Performance of Vanadium Redox Flow Battery. Issue 12 (1st January 2019) - Moon, Seongeun; Kwon, Byeong Wan; Chung, Yongjin; Kwon, Yongchai
Abstract : Bismuth sulfate (BiOS) is doped on acidified carbon nanotube (ACNT) (BiOS-ACNT) using sulfuric acid treatment and this is used as catalyst to improve the performance of vanadium redox flow battery (VRFB). Its catalytic activity is compared with that of pure CNT and ACNT. Regarding the redox reactivity of vanadium ions, BiOS-ACNT whose weight ratio is 1:3 exhibits the best catalytic activity and reaction reversibility for both VO 2+ /VO2 + and V 2+ /V 3+ reactions because the abundant oxygen atoms are well produced during the conversion of bismuth (Bi) nanoparticle into BiOS, and they act as active site for promoting the reactions of VO 2+ /VO2 + and V 2+ /V 3+ . These are confirmed by calculating kinetic parameters, such as electron transfer rate constant and diffusion coefficient, while BiOS-ACNT shows the best values (0.21 s −1 and 6.46 × 10 −8 cm 2 s −1 ). In VRFB including BiOS-ACNT, the performance of BiOS-ACNT VRFB is enhanced with voltage and energy efficiencies of 87.6 and 81.9% at 80 mA cm −2 . Furthermore, in 50 cycle test of 120 mA cm −2, BiOS-ACNT VRFB shows lower overpotential (0.2 V) and capacity loss rate (0.04% cycle −1 ) than other VRFBs. This proves that BiOS-ACNT is beneficial for enhancements in the performance and long-term stability of VRFB.